2018
DOI: 10.3390/molecules23040946
|View full text |Cite
|
Sign up to set email alerts
|

Zeta Potential of Beta Zeolites: Influence of Structure, Acidity, pH, Temperature and Concentration

Abstract: Measurements of the zeta potential of solid heterogeneous supports are important for preparation of metal supported catalysts and for shaping zeolites into extrudates. In the current work, different types of heterogeneous support materials such as SiO2, Al2O3, and a range of beta zeolites of different silica- to-alumina ratio were analysed. It was observed that parameters such as temperature, pH and acidity significantly affect the zeta potential. In several instances, depending on the materials’ acidity and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 52 publications
4
22
0
2
Order By: Relevance
“…The EDL should be different with the same surface structure in pores of the adsorbent and on its surface of micro- and nanoparticles. Parameters such as pH, temperature, and solution composition can have impacts on the structure of the EDL on the particle surface and in pores of different sizes [ 42 , 43 , 44 , 45 , 46 , 47 ]. In the next step, the SS-FA was rinsed with distilled water in order to obtain a pH of 7 of the dispersion system.…”
Section: Resultsmentioning
confidence: 99%
“…The EDL should be different with the same surface structure in pores of the adsorbent and on its surface of micro- and nanoparticles. Parameters such as pH, temperature, and solution composition can have impacts on the structure of the EDL on the particle surface and in pores of different sizes [ 42 , 43 , 44 , 45 , 46 , 47 ]. In the next step, the SS-FA was rinsed with distilled water in order to obtain a pH of 7 of the dispersion system.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that in some cases acidic or alkaline extracting phases were employed, the time of contact of 5 min with the loaded zeolite (see Section 3.3 ) is too brief to induce structural degradation. Moreover, it should be considered that, in the studied pH range, it has been reported that zeolites [ 42 , 44 ] do not undergo degradation.…”
Section: Resultsmentioning
confidence: 99%
“…The principle of the zeta measurement is substantive because it measures a proportion of the analyzed sample (relative particle amount as a percentage where the total amount of particles is 100%). Thus, the large amount of particles measured through the zeta analysis justified the measurement of the particle proportion [29][30][31][32][33] . Unlike zeta potential measurements, a low PDI indicates a small and uniform size distribution of particles, whereas a high PDI value indicates a large and irregular distribution of particle sizes 34 .…”
Section: Resultsmentioning
confidence: 99%